MG-139 Non-penetrance, variable expressivity or non pathogenicity of abcc9 dilated cardiomyopathy (DCM) mutation in 3 generation kindred. (4th December 2015) - Dyack, Sarah; Crowley, Amy; Gray, Christopher; Hathaway, Julie; Marcadier, Janet; Van Iderstine, Natasha; Harrison, Karen; Gardner, Martin
Abstract : Mutations in ABCC9 have been implicated in the development of Cantu syndrome, Brugada syndrome and isolated dilated cardiomyopathy (DCM). ABCC9 codes for the SUR2A subunit of the cardiac K(ATP) channel. Missense mutations are implicated in the development of Cantu as gain of function effects, but a null mutation has been reported in the literature as causing isolated DCM. We report a large family with an ABCC9 mutation. The female proband presented at age 63 with severe bradycardia requiring a pacemaker, and was diagnosed at age 67 with DCM. A heterozygous null mutation in ABCC9, c.169C >T (p. Gln57X) in exon 2 was discovered and was reported in 2009 as presumed pathogenic. Her obligate carrier brother had severe DCM in his mid 50's requiring cardiac transplantation. Her obligate carrier sister is reported to have a pacemaker in her 60's with no DCM. In the subsequent generation, a male with the mutation at age 46 had a normal LV size and function, with a reported mild concentric LVH. Four other mutation carriers (ages 32, 40, 42 and 59) have no echocardiographic evidence of DCM. Although non-penetrance and variable expressivity could explain the large number of unaffected mutation carriers in the family, it remains unclear if this ABCC9 mutation is responsible for the DCM in this family. Despite mutations in this gene being reported in 2004 as causing DCM, there are few subsequent reports of affected families, and no reports of familial segregation. This family illustrates the difficulty in interpreting molecular results when literature is limited and published before more stringent criteria for pathogenicity were established. The importance of careful family follow up of purported genetic mutations cannot be overstated. A critical literature review and correlating familial genotype and phenotype information should be performed when interpreting molecular genetic test results.